Communal Intellectual Property Rights and Creative Industry Development Through Integration Patterns - Zulkifli Zulkifli; Almusawir Almusawir; Andi Tira (Unissula, 2025)
Traditional communal intellectual property systems face significant limitations that restrict their economic potential, primarily due to inadequate documentation frameworks and weak ownership security. Simultaneously, creative industries struggle to effectively leverage communal intellectual property resources for innovation, limiting the sustainable economic benefits that could be shared by both traditional communities and creative sector actors. This study examines the potential synergies between communal intellectual property frameworks and creative industry development, aiming to preserve cultural authenticity while promoting economic viability for stakeholders. Using a qualitative research approach, data were collected through literature reviews and structured interviews with key stakeholders in South Sulawesi Province. Findings reveal critical gaps in current communal intellectual property documentation and legal recognition, which hinder effective utilization of cultural assets for economic purposes. Creative industry actors demonstrated strong interest in integrating communal intellectual property but were constrained by the lack of formal legal frameworks, standardized documentation, and collaborative mechanisms. Barriers identified include inefficient intellectual property registration processes and limited community engagement protocols, which weaken equitable benefit-sharing. Nevertheless, successful integration models were observed where communities retained cultural control while enabling structured access for creative industries through cooperative partnerships. The study concludes that legal reforms, standardized documentation, and inclusive governance are essential to foster sustainable communal intellectual property-creative industry collaboration, offering a viable pathway to enhance cultural preservation and drive economic growth in both sectors.